Bioenergy production: are the objects realistic?? - Csipkés, Margit (Acta Agraria Debreceniensis, 2008)
Currently we do not have the possibility to define our energy reserves, since we do not know the magnitude of extant material resources. The known petroleum (crude) supply will be sufficient for about 100 years at the longest, and according to the latest estimates in 2008 we will reach and even exceed the maximum level of oil extraction, and after this it is going to decrease.Hungary has good givens to go upon the way of sustainable energy economy according to experts, however a coherent government policy that lasts for not just one period is essential, and a sound economic- and agricultural policy is needed as well. According to the FVM’s under-secretary in Hungary more than 1 million hectares can be disposable for energy crop production. This would mean that 20 percent of the fields would be taken away from food production and on these fields energy crops would be grown. But we also have to take into consideration that the increase in energy plant production could happen at the expense of food production. If we would like to ensure the food for Hungary’s population from national sources we have to make calculations in determining energy need. In my research I set out the objective to determine the level of that specific turnover and marginal cost which supports the profitability of grain cultivation. With these indicators it is possible to analyze the economy and competitiveness of growing energy crops in the region of the North Plain. The alternatives of using cereals and rational land use should be also considered. A developing bio-fuel program can be a solution for the deduction of excess grain that is typical in Hungary for several years in the cereals sector. The pressure on the national market caused by excess grain can be ceased or moderated, and therefore the storage problems would decrease as well.